Impairments among DSM-5 eating disorders: A systematic review and multilevel meta-analysis. (April 2023) - Wilkop, Madeleine; Wade, Tracey D.; Keegan, Ella; Cohen-Woods, Sarah
Abstract: Previous research revealed that people who did not meet full DSM-IV criteria for anorexia nervosa (AN), bulimia nervosa (BN), or binge-eating disorder (BED) but met criteria for eating disorder not otherwise specified (EDNOS) display high levels of psychiatric and physical morbidity commensurate with full criteria eating disorders. The DSM-5 introduced significant changes to eating disorder diagnostic criteria, so the present study aimed to determine whether the revised diagnostic criteria better distinguish between full criteria eating disorders, and other specified feeding or eating disorder (OSFED) and unspecified feeding or eating disorder (UFED). We present a series of meta-analyses comparing eating pathology, general psychopathology, and physical health impairments among those with AN, BN, and BED, compared to those with OSFED or UFED ( n = 69 eligible studies). Results showed significantly more eating pathology in OSFED compared to AN, no difference in general psychopathology, and greater physical health impairments in AN. BN had greater eating pathology and general psychopathology than OSFED, but OSFED showed more physical health impairments. No differences were found between BN and purging disorder or low-frequency BN, or between BED and OSFED. Findings highlight the clinical severity of OSFED and suggest the DSM-5 criteria may not appropriately account for these presentations. Highlights: Multilevel meta-analyses compared impairments among DSM-5 eating disorders (EDs). Other specified EDs have high physical and psychiatric morbidity. DSM-5 does not differentiate between EDs in terms of impairment. Diagnostic criteria need refining to facilitate proper ED diagnosis and treatment.